AUDIT COMMITTEE CAPABILITY, INDEPENDENT COMMISSIONERS, AND FINANCIAL PERFORMANCE: DOES CORPORATE GREENWASHING IMPAIR OVERSIGHT QUALITY? - Moh. Ubaidillah (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2026)
This study aims to examine the influence of independent directors and audit committee capabilities on financial performance, and to analyses the role of corporate greenwashing (ESG decoupling) as a moderating variable in this relationship. Using an explanatory quantitative approach with purposive sampling, the study sample comprises 50 listed companies in the Consumer Non-Cyclicals sector on the Indonesia Stock Exchange (IDX) over the period 2021–2025, resulting in a total of 250 firm-year observations. Secondary data, comprising financial and governance reports, were extracted from the IDX, whilst ESG scores were obtained from the Refinitiv Eikon and Bloomberg databases, which were subsequently analysed using Moderated Regression Analysis (MRA) via SPSS software. The results of the empirical testing indicate that, in part, Independent Commissioners and Audit Committee Capability have a significant positive effect on Financial Performance (Return on Assets), confirming the effectiveness of governance oversight functions in mitigating agency costs. However, the interaction model test demonstrated that corporate greenwashing significantly weakens the positive influence of independent directors and audit committee capabilities on financial performance. The gap between sustainability disclosures and high sustainability performance gives rise to a new form of non-financial information asymmetry that limits the effectiveness of audit committee oversight and reduces the scepticism of independent board members, thereby reducing the efficiency of corporate capital allocation and company profitability. The implications of this research urge regulators to establish mandatory third-party verification policies to mitigate the risk of manipulation of non-financial reporting in Indonesia.